Fitness of Races 0 and 1 of Phytophthora parasitica var. nicotianae - Sullivan, M J (Plant disease, 2005)
Deployment of tobacco (Nicotiana tabacum) varieties with complete resistance to race 0 of Phytophthora parasitica var. nicotianae has led to a rapid increase in the field populations of race 1 in North Carolina. In a field study, population levels of race 1 decreased relative to race 0 when cultivars with partial resistance to both races were planted, suggesting that race 1 isolates were less fit than race 0 isolates. Experiments were conducted to quantify differences in aggressiveness and survivability of the two races. Tobacco varieties with low, moderate, or high levels of partial resistance were inoculated with 60 pathogen isolates, and symptom development was monitored for 3 weeks. Race 0 isolates were more aggressive than race 1 isolates on cultivars with moderate or high levels of partial resistance; incubation periods were shorter and root rot severity was greater with race 0 isolates. Isolates of race 1, however, caused greater stunting of plants with moderate and high levels of partial resistance than race 0 isolates. Field microplots were infested with either a single race or an equal mixture of each race. Soil samples were collected at the end of two growing seasons and again the following spring. Pathogen populations declined from 40 to 80% during winter months, but population declines for race 0 were lower than for race 1 in each treatment over each winter. Race shifts from race 1 to race 0 that were observed in the presence of cultivars with partial resistance appear to be primarily the result of differences in aggressiveness of the races, with a possible minor effect of enhanced overwintering survival of race 0 compared with race 1